Multinational business finance David K. Eiteman, Arthur I. Stonehill and Michael H. Moffett. - Eiteman, David K.; Stonehill, Arthur I.; Moffett, Michael H. (Pearson, 2021)
Renowned for its authoritative, comprehensive coverage of contemporary international finance, this text trains the leaders of tomorrow's multinational enterprises to recognise and capitalise on the unique characteristics of global markets.